A case of recurrent bilateral uveitis independently associated with dabrafenib and pembrolizumab therapy - Taylor, Stanford C. (Am J Ophthalmol Case Rep, 2016)
PURPOSE: To report the case of an adult female who presented on different occasions with recurrent uveitis provoked by initiating therapy of two recently approved agents, dabrafenib and pembrolizumab, for treatment of metastatic melanoma. OBSERVATIONS: A 61 year old female presented with bilateral anterior uveitis after initiating therapy with dabrafenib for advanced metastatic melanoma. Her symptoms resolved and exam improved with oral and topical steroid therapy. Months later, she was started on pembrolizumab and transitioned off dabrafenib. Within days of starting pembrolizumab, she developed recurrent bilateral uveitis. This responded to escalating doses of topical and oral corticosteroid therapy and resolved following discontinuation of pembrolizumab. Nine months later, our patient received her third dose of pembrolizumab due to further progression of melanoma and within three days developed blurry vision, photophobia and subsequent ophthalmologic exam demonstrated bilateral panuveitis. CONCLUSIONS AND IMPORTANCE: Dabrafenib and pembrolizumab therapy have both previously been associated with uveitis. Here, we document a case of a woman who developed acute uveitis in response to beginning therapy with dabrafenib and then later developed acute uveitis soon after initiating pembrolizumab. To our knowledge, this is the first time this uncommon side-effect has been reported in the same patient after receiving sequential targeted agents and checkpoint inhibitors.